The global crisis, government contracts, licensing and corruption - Halil D. Kaya (SocioEconomic Challenges, 2023)
This paper summarizes the arguments and counterarguments within the scientific discussion on the issue of corruption. The main purpose of the research is to examine the impact of global economic/financial crisis on corruption. We focus on manufacturing firms in the EECA region and examine their activities including bidding for government contracts, applying for an operating license, and applying for an import license. Systematization of the literary sources and approaches for solving the problem indicates that bribes got significantly smaller after the crisis ended. The relevance of this scientific problem decision is that governments’ efforts to improve the overall business environment when facing an economic/financial crisis help reduce corruption. Investigation of corruption in the paper is carried out in the following logical sequence: First, the size of bribes for securing government contracts is examined. Then, the prevalence of bribery during import license application process is examined. Finally, the prevalence of bribery during operating license application process is examined. Methodological tools of the research methods were non-parametric tests that compare the years of 2007 and 2010-2014. The research object is manufacturing firms in the EECA region because they were included in the BEEPS IV and BEEPS V manufacturing surveys. The research empirically confirms and theoretically proves that governments’ actions during an economic or financial crisis affect the size and prevalence of bribery. The research results can be useful for government officials that plan on reducing corruption in their region or country.